Trastornos de personalidad y afrontamiento en mujeres que asisten a la Unidad Judicial Multicompetente de Alausí, período 2017 – 2018. - Escudero Orozco, Andrea Carolina (2018)
The present investigation focused in the analyzes of personality disorders and the coping strategies in women that come to the Multicompetent Judicial Unit of Alausi, it has been made with a sample of 30 women between 20 to 55 years old, taking into consideration inclusion and exclusion criteria; field, descriptive, no experimental methodology was used as well as Microsoft Excel for tab. Millon Multiaxial Inventary II was used for evaluating personality and the Inventory of valuation and coping to evaluate the strategies of coping. Once applied the psychometrics instruments it was shown that the most vulnerable group to this risky situation is between the 38 – 43 years old with the 30%, the predominant personality disorders is the compulsive with 37% which is equivalent to 11 women and the coping strategies used for women victims of gender violence are the cognitive coping strategies focused to emotion and the behavioral coping strategies focused to emotion with 27% equivalent to 8 women. The statistical data reflected that women who have been victims of gender violence had emotional coping strategies, but it must generate and strenghen the behavioral type strategies aim to the situation so that they can face the conflicts of everyday life assertively, this will help to improve self-esteem, to have confidence in themselves and to have a better emotional balance.